PENGARUH INOVASI PRODUK TERHADAP PENINGKATAN KINERJA UMKM OT APPAREL - Ela Diana Saputri; Della Putri Satiya Ningtyas; Nanik Kustiningsih (Journal MISSY (Management and Business Strategy), 2020)
In Indonesia, many UMKM have opened businesses in the fashion sector, one of which is screen printing shirts. Screen printing shirts have become a target for someone to open a business today. So, OT Apparel made screen printing shirts using a DTG (Direct to Garment) printer machine. The main objective of this research is to develop product innovation to improve the performance of UMKM OT Apparel. The problem to be studied is testing the effect of product innovation on OT Apparel performance. By looking at the market share that currently has a lot of competition, entepreneurs have to come up with product innovations to attract the attention of potential consumers. The research method used is a qualitative method with a case study approach. Data collection using the observation method. Based on the results of data analysis, making an innovation, can improve the performance of UMKM OT Apparel. Always follow developments so that the design that are made can be liked by many people. Apart from product innovation, marketing strategies are also needed in orded minimize competitiveness. Therefore OT Apparel continues to improve performance and create the latest product innovation designs.